(untitled) (REMUNOM, 2026)
This study aimed to identify instances of violence perpetrated by coaches in the narratives of female futsal athletes. This is a qualitative study, with data collected through semi-structured interviews with six athletes residing in Juiz de Fora/MG, Brazil. The analysis was conducted using thematic content analysis. The results showed that all participants reported experiencing or witnessing some type of violence in the sporting context, characterized as gender-based violence, symbolic violence, moral harassment, neglect, psychological violence, and physical violence. The normalization of these violent practices was observed, as well as a lack of literacy among the athletes regarding violence in sports. It is recommended to promote training programs focused on the prevention and confrontation of gender-based violence in sports, for both athletes and coaches, contributing to the construction of more ethical, safe, and inclusive sporting environments.